ANALYSIS OF FACTORS INHIBITING THE IMPLEMENTATION OF SMK3 IN THE WIDENING PROJECT OF KAPAS – GLENDENG BRIDGE, BOJONEGORO REGENCY - Ariyanti, Menik; Oetomo, Wateno; Sajiyo, Sajiyo; Wulandari, Esti (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2023)
In construction projects, inadequate implementation of the Occupational Safety and Health Management System (OHSMS) poses risks to the safety and well-being of workers, resulting in decreased performance and compromised project quality. This study focuses on the Kapas-Glendeng bridge widening project in Bojonegoro Regency, identifying key obstacles such as workforce competence, limited experience, insufficient training, and challenges accessing digital information. Additionally, issues related to worker involvement in regulation-making, understanding of Personal Protective Equipment (PPE), reporting procedures, and documentation of work accidents were observed. To address these challenges, the study recommends strategies such as involving untrained workers in competence-building programs, providing apprenticeships for less experienced personnel, implementing comprehensive training information systems, actively engaging workers in project planning, enforcing OHS monitoring systems, ensuring mandatory PPE usage with penalties for violations, and establishing clear procedures for recording and reporting work accidents. This proactive approach aims to enhance OHS implementation and mitigate risks in construction projects.